HUBUNGAN ANTARA GAYA MENGAJAR GURU DENGAN MINAT BELAJAR SISWA SMP DALAM PEMBELAJARAN IPS - Heni Lestari; Yadi Suryadi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study aims to analyze the relationship between teachers’ teaching styles and students’ learning interest in Social Studies learning at SMP Negeri 1 Kayen. The study employed a quantitative approach with a correlational research design. The population consisted of all ninth-grade students at SMP Negeri 1 Kayen, while the sample involved 30 students from class IX E selected through purposive sampling. Data were collected using a Likert-scale questionnaire developed based on indicators of teaching style and students’ learning interest variables. The data were analyzed using IBM SPSS Statistics through normality tests, linearity tests, and Pearson product moment correlation analysis. The results showed that the data were normally distributed and had a linear relationship. However, the correlation analysis revealed a correlation coefficient value of -0.122 with a significance value of 0.522 (>0.05), indicating that there was no significant relationship between teachers’ teaching styles and students’ learning interest. The relationship found was very weak and negative. Observation results indicated that variations in teaching styles, such as discussions and question-and-answer activities, were able to increase students’ participation, but were not strong enough to consistently influence students’ learning interest. The findings suggest that students’ learning interests are also influenced by other factors, including learning motivation, learning readiness, learning environment, and the use of instructional media. ABSTRAK Penelitian ini bertujuan untuk menganalisis hubungan antara gaya mengajar guru dengan minat belajar siswa dalam pembelajaran IPS di SMP Negeri 1 Kayen. Penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian korelasional. Populasi penelitian adalah seluruh siswa kelas IX SMP Negeri 1 Kayen dengan sampel sebanyak 30 siswa kelas IX E yang dipilih menggunakan teknik purposive sampling. Teknik pengumpulan data dilakukan menggunakan angket skala Likert yang disusun berdasarkan indikator variabel gaya mengajar guru dan minat belajar siswa. Data dianalisis menggunakan bantuan IBM SPSS Statistics melalui uji normalitas, uji linearitas, dan analisis korelasi product moment Pearson. Hasil penelitian menunjukkan bahwa data berdistribusi normal dan memiliki hubungan linear. Namun, hasil uji korelasi menunjukkan nilai koefisien korelasi sebesar -0,122 dengan nilai signifikansi sebesar 0,522 (>0,05), sehingga tidak terdapat hubungan yang signifikan antara gaya mengajar guru dan minat belajar siswa. Hubungan yang ditemukan berada pada kategori sangat lemah dan bersifat negatif. Hasil observasi menunjukkan bahwa variasi gaya mengajar seperti diskusi dan tanya jawab mampu meningkatkan keaktifan siswa, tetapi belum cukup kuat memengaruhi minat belajar secara konsisten. Temuan penelitian menunjukkan bahwa minat belajar siswa juga dipengaruhi oleh faktor lain seperti motivasi belajar, kesiapan belajar, lingkungan belajar, dan penggunaan media pembelajaran.